PENGARUH LITERASI KEUANGAN DAN PENGELOLAAN KEUANGAN TERHADAP KINERJA UMKM DI KECAMATAN PASIR LIMAU KAPAS KABUPATEN ROKAN HILIR - ', Risna; ', Ruzikna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This research aims to determine financial literacy and financial management on the performance of MSMEs in Pasir Limau Kapas District, Rokan Hiir Regency. This research uses a quantitative method with an associative type of research with the Statistical Product And Service Solutions (SPSS 25) program. This research uses primary data sources which were carried out by taking a sample of 80 MSME actors. The technique used was Purposive random sampling Sampling. The data analysis technique used Descriptive quantitative analysis is used. This analysis includes validity testing, reliability testing, classical assumption testing, multiple linear regression analysis and hypothesis testing via the t test and f test. The results of this research show that financial literacy has a significant effect on the performance of MSMEs. Then financial management has a significant effect on the performance of MSMEs. And financial literacy and financial management have a significant effect on the performance of MSMEs. Keywords: Financial Literacy, Financial Management, and MSME Performance